2018
DOI: 10.5812/jjhs.77130
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-Producing Ability of Bovine Extraintestinal Pathogenic Escherichia coli and Its Correlation with Attachment Factors

Abstract: Background: Escherichia coli is recognized as a common cause of infection. Long-lasting presence of bacteria on biotic and abiotic surfaces and failure of bacterial eradication are predicted by biofilm production. Some extracellular frills of E. coli can be implicated in productive events, leading to biofilm formation by surface colonization. Objectives: In the present study, correlation of csgA (encoding curli fimbriae) and fimA (encoding a large subunit of type I fimberiae) gene expression with biofilm forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The current study reported that 46.6% of the recovered E. coli isolates were phenotypically positive for biofilm formation. Moori Bakhtiari et al [ 29 ] reported that 53.3% and 16.6% of E. coli isolates were moderately and strongly biofilm producers, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The current study reported that 46.6% of the recovered E. coli isolates were phenotypically positive for biofilm formation. Moori Bakhtiari et al [ 29 ] reported that 53.3% and 16.6% of E. coli isolates were moderately and strongly biofilm producers, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms are dynamic assemblages of microorganisms that adhere to biotic or abiotic surfaces and are characterized by highly specialized interactions between microorganisms. The bacteria are embedded in a matrix of self-produced extracellular polymeric substances (EPS) which allows one to alter phenotypes (e.g., growth rate, gene transcription, and antibiotic resistance) [41,42]. Schematically, a model for the formation of a differentiated and mature bacterial biofilm requires five developmental stages: (i) a reversible attachment of planktonic bacteria to the solid surface; (ii) transition from reversible to irreversible attachment due to production of EPS and/or specific adhesins located on pili and fimbriae, which interact with the surface (e.g., flagella, autotransporter proteins, fimbriae, curli, EPS, and F-type conjugative pilus) [43][44][45]; (iii) early development of biofilm architecture.…”
Section: Biofilmmentioning
confidence: 99%
“…Biofilm-forming bacteria are embedded in a matrix of self-produced slime, constituted by extracellular polymeric substances (EPS) [4]. This growing mode can alter bacterial biological and physiological characteristics, such as reproduction, growth, gene transcription rate, and resistance towards antibiotics [5][6][7]. Schematically, the formation of a differentiated biofilm requires five maturation stages: (i) initial attachment of planktonic bacteria (reversible) to a surface; (ii) production and secretion of EPS and/or other means of docking, and specific adhesins (e.g., flagella, autotransporter proteins, fimbriae, curli fibers, and F-type conjugative pilus) that drive the transitional attachment from reversible to irreversible [8][9][10]; (iii) early-maturing of biofilm architecture as a super cellular structure; (iv) late-maturing of micro-colonies and evolution into a mature biofilm; and (v) detachment of cells from the biofilm and dispersion into the surrounding environment (Figure 1).…”
Section: Introductionmentioning
confidence: 99%